A Comparison of Production Methods of High-Purity Perrhenic Acid from Secondary Resources - Dorota Kopyto; Mateusz Ciszewski; Szymon Orda; Katarzyna Leszczyńska-Sejda; Joanna Malarz; Patrycja Kowalik; Karolina Pianowska; Karolina Goc; Grzegorz Benke; Alicja Grzybek; Dorota Babilas; Piotr Dydo (Separations, 2024)
Methods for obtaining high-purity perrhenic acid (with metallic impurities content below 100 ppm) of a high concentration > 200 g/dm3 and entirely from secondary raw materials were compared. Comparative analyses of three methods were performed: electrodialysis, solvent extraction (research carried out directly as part of the Small Grant project acronym RenMet), and ion-exchange (developed as part of previous projects implemented by Łukasiewicz-IMN). The basic process parameters were selected as comparative indicators: efficiency and selectivity of the process, purity of the obtained product, availability and consumption of raw materials and reagents, equipment necessary to carry out the process, the profitability of the technology, and the ecological aspects, i.e., the possibility of managing the generated solid waste and post-production solutions. Analysis of the verified indicators allowed us to select the most economically and ecologically advantageous method of obtaining high-purity perrhenic acid from secondary raw materials. Its preparation using the ion-exchange method emphasizes the product’s purity and the process’s simplicity, using readily available waste materials and renewable ion-exchange resin, and is based on a sustainable circular economy.